Determinants of routine immunisation coverage among children aged 12–23 months in Adansi South district in the Ashanti region, Ghana - Sem, Samuel (University of Cape Coast, 2023)
The study sought to assess the routine childhood immunisation status (RCIS) and its determinants among children aged 12 – 23 months living in the Adansi South District (ASD) within the Ashanti Region of Ghana. To guide the investigation, five research questions were developed. An analytical cross-sectional survey design with a quantitative methodology was utilised for this study. The census sampling technique was employed to select a total of 3,312 participants. Data collection was conducted using a questionnaire, and the data were analysed using SPSS Version 27.0. The findings revealed a low RCIS, with only 56.8% of children aged 12-23 months in ASD having received routine childhood immunisations. The study identified several factors that influenced RCIS, including the child’s age, the number of children in the family, the marital status of the parents, attendance at antenatal care (ANC), and the number of ANC visits. Maternal occupational status, adequacy of income, the perception of spousal income as adequate and regular, and if it is the sole source of livelihood, household wealth status, and the type of housing for dwelling was found as enabling factors to influence RCIS. Additionally, mothers’ perspectives on the conduct of CWC, distance, hours used, means of transport, satisfaction with service providers' communication, and mothers' perceived attitudes of staff and their perception of vaccines, service providers, and immunisation services influence RCIS.The GHS/DHD of ASD should enhance efforts in conducting comprehensive public awareness and health education campaigns targeting mothers and households. These campaigns should emphasise the benefits of RCI and stress the importance of completing the immunisation schedules.
xvii, 249p;, ill
Keywords: Adansi South District; childhood immunisation; antenatal care; health education campaigns